Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T08:29:35+02:00
1,2+(3i1/4*(-2/5=

1) 1,2+3i1/4*(-2/5)=(wydaje mi się ,że działanie tak powinno wyglądać)=1,2+13/4*(-2/5)=1,2+(-26/20)=1,2+(-1,3)=1,2-1,3=-0,1


2)3i 3/4 * 1i3/5 - ( -1,75)=15/4* 8/5-(-1,75)=6-(-1,75)=6+1,75=7,75

3)-1i1/2* 2i1/3 +3/4 ;0,25 =-3/2*7/3 + 3/4:1/4= -7/2 +3/4 *4/1=-7/2+3=-3,5+3=-0,5

4) 8-3i1/2 * 3i 1/3=8-7/2*10/3=8-35/3=8-11i2/3=-3i2/3



2010-04-11T08:31:11+02:00
1,2+(3i1/4*(-2/5=
1,2 +13/4 *(-2/5)=
1,2 -26/20=
12/10-26/20
24/20-26/20= -2/20=-1/10

3i 3/4 * 1i3/5 - ( -1,75)=
15/4 *8/5 +1 3/4=
6+7/4=7,75


-1i1/2* 2i1/3 +3/4 ;0,25 =
-3/2 *7/3 +3/4*4=
-7/2+3= -1/2
8-3i1/2 * 3i 1/3=
8 - 7/2 *10/3= 8-35/3
=24/3-35/3= -11/3= -3 2/3